Synthesis and Characterization of Modified Kaolin-Bentonite Composites for Enhanced Fluoride Removal from Drinking Water - Ebenezer Annan; Emmanuel Nyankson; Benjamin Agyei-Tuffour; Stephen Kofi Armah; George Nkrumah-Buandoh; Joanna Aba Modupeh Hodasi; Michael Oteng-Peprah (Advances in Materials Science and Engineering)
Fluoride-contaminated drinking waters are known to cause severe health hazards such as fluorosis and arthritis. This paper presents the encapsulation of iron oxide nanoparticles in kaolin-bentonite composites adsorbents (KBNPs) for the removal of fluoride from drinking water by adsorption compared with kaolin-bentonite composite (KB). Adsorbents with an average weight of ∼200 mg and ∼7 mm diameter (granules) were prepared in the ratio of 10 : 10 : 0.1 for kaolinite, bentonite, and magnetite nanoparticles, respectively. The granules were air-dried and calcined at 750°C and contacted with 2 mg/L sodium fluoride solution at varying time periods. The adsorbents were characterized using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) formulation, and Brunauer–Emmett–Teller (BET), whereas the adsorption mechanism and the kinetics were explained using the Langmuir isotherm, Freundlich models, and pseudo-first-order and pseudo-second-order models. The results showed that the BET surface areas for the granules were 10 m2/g and 3 m2/g for KBNPs and KB, respectively. The SEM images for the adsorbents before and after adsorption confirm the plate-like morphology of kaolin and bentonite. The FTIR analyses of bentonite (3550 cm−1–4000 cm−1) and kaolin (400–1200 cm−1) correspond to the structural hydroxyl groups and water molecules in the interlayer space of bentonites and the vibrational modes of SiO4 tetrahedron of kaolin, respectively. The KBNPs composites also recorded a fluoride removal efficiency of ∼91% after 120 minutes compared with 64% for KB composites without Fe3O4 nanoparticles. The adsorptions of fluoride by the KBNPs and KB granules were found to agree with the Freundlich isotherm and a pseudo-second-order kinetic model, respectively. The results clearly show that the impregnation of clays with magnetite nanoparticles has significant effect in the removal of fluoride, and the implication of the results has been discussed to show the impact of clay-magnetite nanoparticles composites in the removal of fluoride from contaminated water.